ANALISIS PARTISIPASI KELOMPOK RENTAN DALAM VAKSINASI COVID-19 DI PUSKESMAS MUNGO KABUPATEN LIMA PULUH KOTA - Azmil Fadhli; Lince Magriasti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
Community participation is the participation or involvement of the community in the process of identifying problems, identifying the potential that exists in the community, selecting and making alternative decisions for problem solving solutions, implementing efforts to overcome problems, and also community involvement in the process of evaluating change. that happened. In this study, it is more focused on community participation which is classified as a vulnerable group, vulnerable groups are all people who face obstacles or limitations in enjoying a decent standard of living. The purpose of this research is to find out how to analyze participation, what are the obstacles faced and what efforts are made to increase the participation of vulnerable groups to Covid-19 vaccination at the Mungo Health Center, Lima Puluh Kota Regency. This research is a quasi-qualitative or quasi-qualitative research. Techniques and data collection through interviews and documentation studies. This study uses the theory according to Ahmad Mustanir and Partisan Abadi (2017), the author examines the analysis of the participation of vulnerable groups in the covid-19 vaccination at the Mungo Public Health Center, fifty cities, seen from 4 indicators of community participation, 1) participation, 2) participation, 3 ) contribution, 4) willingness. The results of this study indicate that the participation of vulnerable groups in participating in the Covid-19 vaccination is still lacking.